Sadako and the thousand paper cranes - Coerr, Eleanor (Putnam, 1977)
Hospitalized with the dreaded atom bomb disease, leukemia, a child in Hiroshima races against time to fold one thousand paper cranes to verify the legend that by doing so a sick person will become healthy.